2018
DOI: 10.55766/oxmz7550
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chinese University EFL Students’ Speaking Skills through Digital Storytelling

Abstract: The present study aims to investigate whether a 12-week digital storytelling (DST) intervention could improve Chinese university EFL students’ speaking skills. The entire population for this study consisted of 100 English major undergraduates from 2 intact classes of EFL students that were taught by the same teacher. Each class contained 50 participants. The experimental group students participated in the DST intervention and were exposed to the DST activities both inside and outside classroom while the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This finding was consistent with the prior study by (Fitri et al, 2021;Riani et al, 2021;Aziz & Husnawadi, 2020) which showed the majority of the students perceived the implementation of DST-based task positively. Aziz & Husnawadi, 2020;Wei et al, 2018). Aziz & Husnawadi (2020) asserted that digital storytelling-based tasks increase motivation and interpersonal relationships.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was consistent with the prior study by (Fitri et al, 2021;Riani et al, 2021;Aziz & Husnawadi, 2020) which showed the majority of the students perceived the implementation of DST-based task positively. Aziz & Husnawadi, 2020;Wei et al, 2018). Aziz & Husnawadi (2020) asserted that digital storytelling-based tasks increase motivation and interpersonal relationships.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Aziz & Husnawadi (2020) asserted that digital storytelling-based tasks increase motivation and interpersonal relationships. Simultaneously, Wei et al (2018) promoted that during the instructional process the student's interests were increased as well as they were motivated to practice their English. Whilst, the research by Zakaria and Aziz (2019) also stated a positive outcome where digital storytelling inspires students to study as it help them learn the target language.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When students write their own scripts, record their own voices, mix with different types of multimedia, and present their stories to the audience, they interact with the language and use the target language in authentic ways, fostering meaningful learning (Kajder, 2006;Rance-Roney, 2008). Various studies in the literature present the use of DS for the development of such language skills as Writing (Balaman, 2018;Sepp & Bandi-Rao, 2015;Sudarmaji & Mulyana, 2020;Tanrıkulu, 2020) Reading (Anggeraini & Afifah, 2017;Rahimi & Yadollahi, 2017;Yoon, 2013), Listening (Cigerci & Gultekin, 2017;Loniza, Aslina, & Mazlina, 2018;Tahriri, Tous, & MovahedFar, 2015), and Speaking (Baghdasaryan, 2012;Wei, Siriyothin, & Lian, 2018;Yang, Chen, & Hung, 2020). Baghdasaryan (2012) examined the use of DS as homework for developing learners' speaking skills and revealing their attitude towards the program applied in a mixed-method research and concluded that DS provided significant gains in learners' oral production and learners developed positive attitude towards DS use as homework.…”
Section: Studies On the Use Of Digital Storytelling In Language Learningmentioning
confidence: 99%
“…Baghdasaryan (2012) examined the use of DS as homework for developing learners' speaking skills and revealing their attitude towards the program applied in a mixed-method research and concluded that DS provided significant gains in learners' oral production and learners developed positive attitude towards DS use as homework. Wei, Siriyothin, and Lian (2018) investigated Chinese EFL major students' speaking skills in a 12-week DS intervention with 100 students. The experimental group students participated in DS intervention as in-and-out of classroom activities and the control group students received conventional whole-class instruction.…”
Section: Studies On the Use Of Digital Storytelling In Language Learningmentioning
confidence: 99%